Peran Kurikulum Merdeka Dalam Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa Sekolah Dasar - Moch. Syakroni; Pratiwi, Vina Erni; Muhammad Farhanudin (Jurnal PEKA (Pendidikan Matematika), 2026)
ABSTRACT: This study aims to systematically examine the role of the Independent Curriculum in improving elementary school students’ critical mathematical thinking skills. This study used a sytematic literature review method to review 13 scientific articles published between 2020 and 2025. The analysis revealed three main findings. First, six article (46.2%) demonstrated the effectiveness of the Independent Curriculum in developing critical thinking skills through contextual, reflective, and student-centered learning. Second, two articles (15.4%) highlighted the effectiveness of Discovery Learning and Project-Based Learning (PjBL) models in stimulating students' analytical and exploratory thinking skills. Third, five articles (38.4%) identified implementation obstacles, primarily teachers' limited understanding of the principles of the Independent Curriculum and the lack of ongoing training and mentoring programs. Overall, the results of this study confirm that the Independent Curriculum has significant potential to develop students' critical mathematical thinking skills if combined with improved teacher pedagogical competence, institutional support, and the implementation of adaptive and contextual learning strategies.  ABSTRAK: Penelitian ini bertujuan untuk menelaah secara sistematis peran Kurikulum Merdeka dalam meningkatkan kemampuan berpikir kritis matematis siswa sekolah dasar. Kajian ini menggunakan metode Systematic Literature Review terhadap 13 artikel ilmiah yang diterbitkan pada periode 2020–2025. Hasil analisis menunjukkan tiga temuan utama. Pertama, terdapat 6 artikel (46,2%) yang menunjukkan bahwa Kurikulum Merdeka efektif dalam mengembangkan kemampuan berpikir kritis melalui pembelajaran yang kontekstual, reflektif, dan berpusat pada peserta didik. Kedua, 2 artikel (15,4%) menyoroti efektivitas model pembelajaran Discovery Learning dan Project Based Learning (PjBL) yang mampu menstimulasi kemampuan berpikir analitis dan eksploratif siswa. Ketiga, 5 artikel (38,4%) mengidentifikasi kendala implementasi, terutama keterbatasan pemahaman guru terhadap prinsip Kurikulum Merdeka serta kurangnya program pelatihan dan pendampingan berkelanjutan. Secara keseluruhan, hasil kajian ini menegaskan bahwa Kurikulum Merdeka memiliki potensi signifikan dalam mengembangkan kemampuan berpikir kritis matematis siswa apabila diimbangi dengan peningkatan kompetensi pedagogis guru, dukungan institusional, serta penerapan strategi pembelajaran yang adaptif dan kontekstual.